Prehabilitation in the lung cancer pathway: a scoping review - Kelly Wade-Mcbane; Alex King; Catherine Urch; Julian Jeyasingh-Jacob; Andrew Milne; Clair Le Boutillier (BMC Cancer, 2023)
Abstract Background Lung cancer is the third most common type of cancer in the UK. Treatment outcomes are poor and UK deaths from lung cancer are higher than any other cancer. Prehabilitation has shown to be an important means of preparing patients both physically and psychologically for cancer treatment. However, little is understood about the context and mechanisms of prehabilitation that can impact physiological and psychological wellbeing. Our aim was to review and summarise primary research on prehabilitation in the lung cancer pathway using a realist approach. Methods A scoping review of empirical primary research was conducted. Five online medical databases from 2016 – February 2023 were searched. All articles reporting on prehabilitation in lung cancer were included in the review. For this review, prehabilitation was defined as either a uni-modal or multi-modal intervention including exercise, nutrition and/or psychosocial support within a home, community or hospital based setting. A realist framework of context, mechanism and outcome was used to assist with the interpretation of findings. Results In total, 31 studies were included in the review, of which, three were published study protocols. Over 95% of studies featured an exercise component as part of a prehabilitation programme. Twenty-six of the studies had a surgical focus. Only two studies reported using theory to underpin the design of this complex intervention. There was large heterogeneity across all studies as well as a lack of clinical trials to provide definitive evidence on the programme design, setting, type of intervention, patient criteria, delivery, duration and outcome measures used. Conclusion A standardised prehabilitation programme for lung cancer patients does not yet exist. Future lung cancer prehabilitation programmes should take into account patient led values, needs, goals, support structures and beliefs, as these factors can affect the delivery and engagement of interventions. Future research should consider using a conceptual framework to conceptualise the living with and beyond cancer experience to help shape and inform personalised prehabilitation services.